Representaciones y consumo del cuerpo femenino negro en la poesía negrista antillana - Flisek, Agnieszka (Romanica Silesiana, 2021)
In Cuban and Puerto Rican negrista poetry (no matter what ethnicity the author is to be ascribed to) the black or mulatto females are depicted uniquely in accordance to their external attributes. Works by Nicolás Guillén and Luis Palés Matos draw attention to their fractured beauty and the artificiality of their body, which tends to acquire purposes the white body (the vehicle for reason) lacks, namely, that of augmented sexuality. In this meaning, their bodies represent the desired ones. Nonetheless, the configuration of racial identity through physique implies that the female subject is severed from its specific historical circumstances: the black or mulatto female body serves as the national symbol. The picturesqueness of African origin, which these females incarnate, invokes untamed and savage sensuality, hints at its ludic and festive nature (Jáuregui, 2008), and furthermore replaces and suppresses the harsh reality of a subject exploited by agroindustry and (neo)colonial sugar companies that operated within the area. In other words, such depiction disguises the fact that they are only labour bodies. From the perspective of such sexualized and racialized portrayal of female corporeality, the aim of the paper is to answer Hélène Cixous’s dilemma: “Where is she?”